"AUTOEUROPA and the struggle for industrial democracy in Portugal: the success and limitations of a Workers Commission" - Stoleroff, A.; Chora, A. (ISA RC10 Conference: "Democracy and Participation in the 21st Century", 2017)
The Portuguese labor movement has, on the whole, neglected participatory conceptions and workplace practices of industrial democracy in favor of the trade union development of collective bargaining, tri-partite concertation and political mobilization (Stoleroff 2016). In this context, the experience of the automobile assembly plant, Autoeuropa, and its Workers Commission has been referred to as an exceptional case that has, nevertheless, had a significant, if not decisive, influence in shaping the present day model of Portuguese employment relations, due especially to its effective role in decentralized bargaining of working conditions. This paper represents a collaborative effort on the part of the long-term coordinator of this Workers Commission and an academic sociologist to assess the success and limitations of the experience of this Commission with regard to the representation of the plant’s workers. It will look at how the Commission’s experience stands up to well-known problems of workers’ participation and work place democracy. To do so, it will situate the context in which the Council emerged, the human resource and management perspectives of the company, the policies and practice of the Commission with regard to bargaining and its relationship with union organizations in the company. It will conclude by seeking to understand the relevance of this experience in the Portuguese and international context.